Volume 8: Heat Transfer, Fluid Flows, and Thermal Systems, Parts a and B 2007
DOI: 10.1115/imece2007-43471
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Two-Phase Refrigerant and Refrigerant-Oil Flow in a Microchannel

Abstract: Visualizations of adiabatic two-phase refrigerant flow in a glass channel of diameter 0.5 mm have been made for three refrigerants: R134a, Propane (R290), and Ammonia (R717), representing a wide span of fluid properties, which covers most of the refrigerants commercially in use. In these visualizations four flow regimes were observed: bubble-slug, slug, slug-annular, and annular. These flow regimes were compared to various flow maps, including some developed for small channels. Flow visualizations were also ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In recent years, a few studies [7][8][9][10][11] have developed flow regime maps for boiling in microchannels using similar axes as conventional maps with flow regime definitions pertinent to microscale boiling, and have shown that flow regime maps developed for larger tubes are inapplicable for predicting flow regime transitions in microchannels. Flow regime maps for adiabatic two-phase flow in microchannels have also been proposed through high-speed visualizations [12][13][14];…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few studies [7][8][9][10][11] have developed flow regime maps for boiling in microchannels using similar axes as conventional maps with flow regime definitions pertinent to microscale boiling, and have shown that flow regime maps developed for larger tubes are inapplicable for predicting flow regime transitions in microchannels. Flow regime maps for adiabatic two-phase flow in microchannels have also been proposed through high-speed visualizations [12][13][14];…”
Section: Introductionmentioning
confidence: 99%
“…In order to readily illustrate the effect of channel size on the transitions between different flow regimes, the lines representing transition from bubbly or slug flows to intermittent churn/wispy-annular or churn/annular flows are plotted for the six microchannel widths in Figure 15 not suitable for predicting the boiling in microchannels as also discussed in the literature (Hetsroni et al 2003, Huo et al 2004, Revellin et al 2006, Field and Hrnjak 2007. In general, five flow regimes -bubbly, slug, churn, wispy-annular, and annular flow -are identified.…”
Section: Effect Of Channel Dimension On Flow Regime Transitionsmentioning
confidence: 99%
“…Field and Hrnjak (2007) showed that the flow maps developed for large channels were not suitable for prediction of the flow regimes in microchannels; also, flow maps were dependent on the specific fluid for which they were developed. Despite the inability of macroscale boiling maps or adiabatic two-phase flow regime maps to predict the flow patterns for boiling in microchannels, a review of the literature shows a dearth of investigations into flow regime maps specifically targeted at microchannels undergoing flow boiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow visualization has been employed to record the flow patterns under different flow conditions and to understand differences from the boiling regimes in conventional-sized channels [7,8,9,10,11,12,13,14,15]. However, systematic research on the effect of channel size and mass flux on the flow patterns during boiling in microchannels has not been performed.…”
Section: Introductionmentioning
confidence: 99%